2012
DOI: 10.1152/advan.00132.2011
|View full text |Cite
|
Sign up to set email alerts
|

Teaching nutritional biochemistry: an experimental approach using yeast

Abstract: In this report, we present a practical approach to teaching several topics in nutrition to science students at the high school and college freshmen levels. This approach uses baker's yeast (Saccharomyces cerevisiae) as a biological system model. The diameters of yeast colonies, which vary according to the nutrients present in the medium, can be observed, compared, and used to teach metabolic requirements. The experiments described in this report show simple macroscopic evidence of submicroscopic nutritional ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…Patro 18 suggested a teaching strategy that combines simple experiments, use of molecular models to distinguish cellular respiration; use of an animated video, questionnaires, and a final evaluation by means of the elaboration of a poster. Alonso & Stella 19 proposed to teach nutrition using yeasts; Figueira and Rocha 20 and Ross et al 21 suggested a problem‐based approach or a role‐playing strategy, respectively. Lubkowitz et al 22 highlighted a series of questions and experiences to follow the path of the carbon atoms in the biosphere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patro 18 suggested a teaching strategy that combines simple experiments, use of molecular models to distinguish cellular respiration; use of an animated video, questionnaires, and a final evaluation by means of the elaboration of a poster. Alonso & Stella 19 proposed to teach nutrition using yeasts; Figueira and Rocha 20 and Ross et al 21 suggested a problem‐based approach or a role‐playing strategy, respectively. Lubkowitz et al 22 highlighted a series of questions and experiences to follow the path of the carbon atoms in the biosphere.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless the teaching resources and strategies used to teach the carbon cycle, [17][18][19] the physiological model of blood glucose uptake and homeostasis, 20,[22][23][24][25][26][27][28][29][30] and the physiological model of the availability of metabolites [1][2][3]25,26,32,33 the important thing is that the students manage to construct biochemical meanings inserted in models [35][36][37][38][39] that holistically encompass the CHM.…”
Section: Final Remarksmentioning
confidence: 99%
“…Se extrajo una pequeña porción del paquete, se colocó en 10 ml de agua destilada estéril y se sembró en medio sólido para aislar colonias. Estas colonias son la fuente de inoculo de todos los experimentos, ya que aseguran la ausencia de contaminación [13,14] .…”
Section: Materiales Y Métodos 21 Célulasunclassified
“…Observación del efecto reductor de N-Acetilcisteína en el metabolismo de levaduras reemplazados por otros de menor costo como azúcar de mesa, 2% p/v; caldo de carne filtrado 10 % p/v, levadura de cerveza en polvo, suplementos nutricionales de aminoácidos, etc [13,14]. El agar puede ser reemplazado por el ofrecido en comercios de productos dietéticos utilizando la misma concentración.…”
Section: /06/2016unclassified